A NOVEL PRESENTATION OF PERES GATE (PG) IN QUANTUM-DOT CELLULAR AUTOMATA(QCA) - Sarker, Angona; Bahar, Ali Newaz; Biswas, Provash Kumar; Morshed, Monir (European Scientific Journal, ESJ, 2014)
QCA technology is a possible substitution for semiconductor-based technology. This paper presents a novel design of a Quantum-dot Cellular Automata (QCA) Peres Gate (PG) and its simulation. Peres Gate (PG) is a reversible logic gates. Reversible logic gates are attracting a lot of attention due to their zero power dissipation under ideal conditions. Reversible logic circuits are useful for constructing quantum computers.